High-resolution phylogenetic analysis of hepatitis C virus adaptation and its relationship to disease progression. - Sheridan, I; Pybus, O; Holmes, E; Klenerman, P (2004)
Hepatitis C virus (HCV) persists in the majority of those infected despite host immune responses. Evidence has accrued that selectively fixed mutations in the envelope genes (E1 and E2) are associated with viral persistence, particularly those that occur within the first hypervariable region of E2 (HVR1). However, the individual amino acid residues under selection have not been identified, nor have their selection pressures been measured, despite the importance of this information for understanding disease pathogenesis and for vaccine design. We performed a high-resolution analysis of published gene sequence data from individuals undergoing acute HCV infection, employing two phylogenetic methods to determine site-specific selection pressures. Strikingly, we found a statistically significant association between the number of sites selected and disease outcome, with the fewest selected sites in fulminant HCV cases and the greatest number of selected sites in rapid progressors, reflecting the duration and intensity of the arms race between host and virus. Moreover, sites outside the HVR1 appear to play a major role in viral evolution and pathogenesis, although there was no association between viral persistence and specific mutations in E1 and E2. Our analysis therefore allows fine dissection of immune selection pressures, which may be more diverse than previously thought. Such analyses could play a similarly informative role in studies of other persistent virus infections, such as human immunodeficiency virus.